Secondary battery, preparation method thereof and electric equipment

Through the localized distribution of electrolyte and intermediate coating design, the problems of stress accumulation and material cracking caused by material expansion and contraction of lithium iron phosphate batteries are solved, and the battery cycle life is extended and the stability is improved.

CN119786725AActive Publication Date: 2025-04-08XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411799611.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-08
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

During the long-term cycle of lithium iron phosphate batteries, stress accumulation and material cracking caused by unit cell expansion and contraction, which in turn led to problems such as decreased electrode conductivity, peeling of active materials, loss of battery capacity and steep increase in impedance.

Method used

By designing locally distributed free and non-free electrolytes, cyclic carbonate compounds such as vinyl carbonate are used to optimize the charging and discharge performance of the battery, and improve stability and cycle life. At the same time, the intermediate coating in the positive electrode sheet is added, and the peeling force from the positive electrode active material layer is controlled to be between 10 N/m and 30 N/m to enhance the adhesion force and suppress the expansion, shrinkage and defiling of the electrode sheet.

Benefits of technology

It achieves the cycle life and stability of lithium iron phosphate batteries without sacrificing battery capacity, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and particularly discloses a secondary battery, a preparation method thereof and electric equipment. The secondary battery comprises a positive pole piece, a negative pole piece, a diaphragm and an electrolyte; the electrolyte comprises a free-state electrolyte and a non-free-state electrolyte, and the non-free-state electrolyte and the free-state electrolyte comprise cyclic carbonate compounds including vinylene carbonate; the mass ratio of the vinylene carbonate in the free electrolyte is m1%, and the total mass ratio of all other cyclic carbonate compounds except the vinylene carbonate is m2%; the mass ratio of the vinylene carbonate in the non-free electrolyte is n1%, and the total mass ratio of all other cyclic carbonate compounds except the vinylene carbonate is n2%; m1, m2, n1 and n2 meet the condition that (m1 / m2)-(n1 / n2) is more than 0 and less than or equal to 0.2; the positive pole piece comprises a positive current collector, and a middle coating and a positive active material layer which are sequentially arranged on the surface of at least one side of the positive current collector, the stripping force between the positive active material layer and the middle coating is S, and S is more than or equal to 10N / m and less than or equal to 30N / m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and a preparation method thereof, and electrical equipment. Background Art

[0002] Lithium-ion batteries with lithium iron phosphate (LiFePO4) positive electrode and graphite negative electrode system have the characteristics of low cost and good safety, and are suitable for the field of electrochemical energy storage. In order to further optimize the efficient use of resources and promote sustainable development, it is necessary to continue to improve the service life of lithium iron phosphate batteries.

[0003] For the LiFePO4 positive electrode, the microscopic manifestation of the lithium stripping / insertion process is the two-phase transformation of orthorhombic LiFePO4 and hexagonal FePO4. When charging is completed, the unit cell volume of FePO4 will be reduced by about 6.8% relative to LiFePO4. However, during the long-term battery cycle, the repeated expansion and contraction of the unit cell will accumulate stress in the particles, leading to material dislocation. The resulting full release of stress will directly cause large-scale cracking of the particles, which is manifested macroscopically as decreased electrode conductivity, stripping of active materials, battery capacity loss, and a sharp increase in impedance.

[0004] Similarly, when the graphite negative electrode is completely embedded with lithium to form LiC6, it will produce a volume expansion of about 10%, and there will also be the generation and expansion of microcracks, material stratification, electrolyte co-embedding, solvent reduction gas production, and a vicious cycle of the above phenomena. Therefore, how to inhibit the cracking of positive and negative active materials is a technical challenge to improve the cycle life of lithium iron phosphate batteries. Generally, the means to inhibit the cracking of positive and negative active materials to improve the cycle life of batteries include: increasing the amount of positive and negative electrode binders used, optimizing the type or degree of polymerization of binders; reducing the coating weight or compaction of positive and negative active materials, and strengthening the coating of active materials. However, these measures will sacrifice the capacity of the electrode, so the method of improving the cycle by optimizing the binder itself and the active material itself is difficult to match the pursuit of high energy density. Summary of the invention

[0005] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present application is to provide a secondary battery and a preparation method thereof, and an electrical device, wherein the secondary battery has a positive electrode active material with good durability and can maintain a long cycle life without sacrificing battery capacity.

[0006] In one aspect of the present application, the present application provides a secondary battery. According to an embodiment of the present application, the secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;

[0007] The electrolyte includes a free electrolyte and a non-free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the diaphragm;

[0008] The non-free electrolyte and the free electrolyte include cyclic carbonate compounds, and the cyclic carbonate compounds include vinylene carbonate;

[0009] Wherein, the mass proportion of vinylene carbonate in the free electrolyte is m1%, and the total mass proportion of other cyclic carbonate compounds except vinylene carbonate is m2%;

[0010] The mass proportion of vinylene carbonate in the non-free electrolyte is n1%, and the total mass proportion of other cyclic carbonate compounds except vinylene carbonate is n2%; m1, m2, n1, n2 satisfy 0<(m1 / m2)-(n1 / n2)≤0.2;

[0011] The positive electrode sheet includes a positive electrode current collector and an intermediate coating and a positive electrode active material layer sequentially arranged on at least one side surface of the positive electrode current collector. The peeling force between the positive electrode active material layer and the intermediate coating is S, and S satisfies 10N / m≤S≤30N / m.

[0012] The present application optimizes the charge and discharge performance of the battery, improves stability and cycle life, etc. by designing the localized distribution characteristics of the free electrolyte and the non-free electrolyte. When the difference (m1 / m2-n1 / n2) between the ratio of the total mass of vinylene carbonate (VC) to all other cyclic carbonate compounds except VC in the non-free electrolyte and the ratio of the total mass of VC to all other cyclic carbonate compounds except VC in the free electrolyte is greater than 0, it can be ensured that the proportion of VC in the free electrolyte is continuously higher than the proportion of VC in the non-free electrolyte. Such a design can maintain sufficient VC in the free electrolyte and bring into play the performance advantages of VC; at the same time, (m1 / m2)-(n1 / n2) is less than or equal to 0.2, which can ensure that VC effectively participates in the repair process of the SEI film, which is conducive to achieving a long cycle life of the battery. In addition, the positive electrode plate is limited to include an intermediate coating, and the peeling force S between the positive electrode active material layer and the positive electrode active material layer is limited to satisfy 10N / m≤S≤30N / m, which can ensure that the positive electrode collector and the positive electrode active material have sufficient bonding force, inhibit the expansion, contraction and film peeling of the plate during the cycle, thereby improving the cycle stability of the battery, and at the same time ensure the electron transmission between the positive electrode collector and the positive electrode active material layer, avoiding higher resistance due to the introduction of the intermediate coating.

[0013] In some embodiments of the present application, m1 and n1 satisfy 0.5≤m1≤5, 0.2≤n1≤3.

[0014] In some embodiments of the present application, the cyclic carbonate compound also includes at least one of propylene carbonate, ethylene carbonate, butylene carbonate, methyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, ethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, propyl vinylene carbonate, 1,2-dipropyl vinylene carbonate, phenyl vinylene carbonate, 1,2-diphenyl vinylene carbonate, vinyl ethylene carbonate, divinyl ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, and 3,3,3-trifluoropropylene carbonate.

[0015] In some embodiments of the present application, the intermediate coating comprises inorganic particles, a conductive agent and a binder;

[0016] And / or, the inorganic particles include at least one of ceramic, boehmite, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide, and zinc oxide;

[0017] and / or, the conductive agent comprises at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers;

[0018] and / or, the binder comprises polyacrylate;

[0019] And / or, the polyacrylate includes at least one of lithium polyacrylate, sodium polyacrylate, and magnesium polyacrylate.

[0020] In some embodiments of the present application, the intermediate coating satisfies at least one of the following conditions:

[0021] The thickness of the intermediate coating is 1 μm-20 μm;

[0022] The bonding force between the intermediate coating and the positive electrode current collector is 260N / m-400N / m.

[0023] In a second aspect of the present application, the present application proposes a method for preparing the secondary battery according to the first aspect, comprising the following steps of injecting an electrolyte:

[0024] The electrolyte used in the first injection is a first electrolyte, the electrolyte used in the second injection is a second electrolyte, the first electrolyte and the second electrolyte independently include cyclic carbonate compounds, and the cyclic carbonate compounds include vinylene carbonate;

[0025] The mass proportion of vinylene carbonate in the first electrolyte is M1%, and the total mass proportion of cyclic carbonate compounds is M2%; the mass proportion of vinylene carbonate in the second electrolyte is N1%, and the total mass proportion of cyclic carbonate compounds is N2%;

[0026] The M1, N1, M2, N2, and S satisfy:

[0027] 15N / m≤M1×S≤50N / m, 100N / m≤N1×S≤200N / m;

[0028] 0.1≤n1<M1<m1<N1≤14.

[0029] Secondary injection flexibly controls the local distribution characteristics of non-free electrolyte and free electrolyte in the initial state of the battery by separating the electrolyte components required in the battery formation stage and the electrolyte components required in the cycle stage. The localized distribution of electrolyte is achieved by controlling n1<M1<m1<N1, and the relationship between M1 and M2 and S is limited to ensure the stability of the intermediate coating of the positive electrode after the cycle, avoiding the degradation of the positive electrode impedance and the significant attenuation of the battery cycle capacity.

[0030] In some embodiments of the present application, the M1, N1, M2, N2, n1, and m1 satisfy at least one of the following conditions:

[0031] M1 / M2-N1 / N2<0;

[0032] 0.01≤M1 / M2≤0.2;

[0033] 0.1≤N1 / N2≤0.6.

[0034] In some embodiments of the present application, the mass ratio of the first electrolyte to the second electrolyte is (6:4) to (8:2).

[0035] In some embodiments of the present application, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5 g / Ah to 5 g / Ah.

[0036] In a third aspect of the present application, the present application provides an electric device. According to an embodiment of the present application, the electric device includes the secondary battery described in the first aspect.

[0037] Therefore, the electrical equipment has all the advantages of the secondary battery, which will not be described in detail here.

[0038] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0039] The embodiments of the present application are described in detail below, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions.

[0040] In one aspect of the present application, the present application provides a secondary battery. According to an embodiment of the present application, the secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;

[0041] The electrolyte includes a free electrolyte and a non-free electrolyte, the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the diaphragm, and the free electrolyte includes an electrolyte outside the pores of the positive electrode sheet, an electrolyte outside the pores of the negative electrode sheet, and an electrolyte outside the pores of the diaphragm;

[0042] The non-free electrolyte and the free electrolyte include cyclic carbonate compounds, and the cyclic carbonate compounds include vinylene carbonate;

[0043] Wherein, the mass proportion of vinylene carbonate in the free electrolyte is m1%, and the total mass proportion of other cyclic carbonate compounds except vinylene carbonate is m2%;

[0044] The mass proportion of vinylene carbonate in the non-free electrolyte is n1%, and the total mass proportion of other cyclic carbonate compounds except vinylene carbonate is n2%; m1, m2, n1, n2 satisfy 0<(m1 / m2)-(n1 / n2)≤0.2;

[0045] The positive electrode sheet includes a positive electrode current collector and an intermediate coating and a positive electrode active material layer sequentially arranged on at least one side surface of the positive electrode current collector. The peeling force between the positive electrode active material layer and the intermediate coating is S, and S satisfies 10N / m≤S≤30N / m.

[0046] The present application adopts the localized electrolyte technology, that is, the non-free electrolyte and the free electrolyte in the battery cell are designed separately. The non-free electrolyte exists in the pores of the material, directly contacts the pole piece and the diaphragm, dominates the formation and repair process of the SEI film, participates in the desolvation effect of active metal ions (such as lithium ions), and directly determines the SEI film impedance R in the battery. SEI and charge transfer resistance R ct ; The free electrolyte exists in the battery cell cavity outside the material pores, and there is no absolute physical barrier with the non-free electrolyte. When the non-free electrolyte is insufficiently consumed, the free electrolyte is automatically absorbed as a supplement through the capillary action of the pole piece and the diaphragm. When the content of a certain component in the non-free electrolyte is higher than that of the free electrolyte, the content of the component decreases after the non-free electrolyte absorbs the free electrolyte; when the content of a certain component in the non-free electrolyte is lower than that of the free electrolyte, the content of the component increases after the non-free electrolyte absorbs the free electrolyte. There are dynamic differences in the electrolyte composition of the two regions during the cycle consumption process, so the component content of the battery during use also changes dynamically.

[0047] The present application defines that the difference (m1 / m2)-(n1 / n2) between the ratio m1 / m2 of the total mass of VC to all other cyclic carbonate compounds except VC in the non-free electrolyte and the ratio n1 / n2 of the total mass of VC to all other cyclic carbonate compounds except VC in the free electrolyte is greater than 0 to ensure that the VC ratio in the free electrolyte is continuously superior to the VC ratio in the non-free electrolyte. Such a design can maintain sufficient VC in the free electrolyte and bring out the performance advantages of VC; at the same time, (m1 / m2)-(n1 / n2) needs to set an upper limit because too large m1 / m2 or too small n1 / n2 means that VC cannot effectively participate in the SEI repair process, which is not conducive to achieving a long cycle life. Specifically, (m1 / m2)-(n1 / n2) can be 0.01, 0.05, 0.1, 0.15, 0.2, etc.

[0048] In addition, the present application specifies that non-free electrolyte and free electrolyte include cyclic carbonate compounds because they can produce cross-linking copolymerization reaction with polymers that have bonding function in the positive electrode to repair broken chains. Commonly used cyclic carbonate compounds include VC, ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), etc. Among them, EC and FEC are connected to other monomers or polymer branches in a linear state after ring opening; VEC is connected by double bonds outside the ring; VC is directly connected by double bonds inside the ring or linearly polymerized after ring opening. From the difference analysis of polymer grafting structure, EC and FEC can greatly improve the flexibility of polymers and increase the density of bonding layer, but the stability and re-grafting ability after chain breaking are poor; VEC can greatly improve the rigidity of polymers, which is conducive to the construction of mesh molecules, but it is easy to break brittlely as the material expands; and VC can balance the improvement of flexibility and rigidity, which can not only maintain the mechanical strength of the bonding layer, but also enable the polymer molecules to have good self-healing ability. Therefore, the present application selects VC with the most balanced flexibility and rigidity structure of the cross-linked product as the main additive.

[0049] The present application also defines that the positive electrode sheet includes a positive electrode current collector and an intermediate coating and a positive electrode active material sequentially arranged on the surface of at least one side of the positive electrode current collector. Since the binder in the positive electrode sheet will age more rapidly with the cycle use of the battery, the binding effect on the internal stress of the particles will decrease, causing cycle degradation, an intermediate coating is added to the positive electrode sheet here, and the peeling force S between the intermediate coating and the positive electrode active material layer is defined to meet 10N / m≤S≤30N / m, which can improve the bonding force between the active material layer and the current collector, inhibit the expansion, contraction, and demolding of the electrode sheet during the cycle, thereby improving the cycle stability of the battery, while not affecting the electron transmission of the current collector and the active material layer, and avoiding excessively high electrode sheet resistance. Specifically, the S may be 10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 15N / m, 16N / m, 17N / m, 18N / m, 19N / m, 20N / m, 21N / m, 22N / m, 23N / m, 24N / m, 25N / m, 26N / m, 27N / m, 28N / m, 29N / m, 30N / m, etc.

[0050] According to the embodiment of the present application, m1 and n1 satisfy 0.5≤m1≤5, 0.2≤n1≤3. If m1 and n1 are too high, the VC content in the free or non-free electrolyte is too high, and the VC continuously and massively participates in the reduction reaction during the cycle, causing R SEI Rapid growth deteriorates the cycle capacity. If m1 and n1 are too low, the VC content in the free or non-free electrolyte is insufficient, and the VC cannot play the role of repairing the positive electrode bonding layer during the cycle, resulting in the peeling of the positive electrode active material after a long cycle, thereby affecting the cycle performance. Specifically, m1 can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc., and n1 can be 0.2, 0.5, 1, 1.5, 2, 2.5, 3, etc.

[0051] According to the embodiments of the present application, the type of the cyclic carbonate compound is not particularly limited. In addition to the VC that must be included, it can also be selected from propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC), methyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, ethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, propyl vinylene carbonate, 1,2-dipropyl vinylene carbonate, phenyl vinylene carbonate, 1,2-diphenyl vinylene carbonate, vinyl ethylene carbonate (VEC) and divinyl ethylene carbonate (DVEC), as well as fluorinated compounds of the above compounds, such as fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), 3,3,3-trifluoropropylene carbonate, etc.

[0052] According to the embodiments of the present application, the composition of the intermediate coating is not particularly limited, and the peeling force between the intermediate coating and the positive electrode active material layer can be within a limited range. As some specific examples, the intermediate coating includes inorganic particles, a conductive agent, and a binder to achieve a strong peeling force between the intermediate coating and the positive electrode active material layer.

[0053] According to some specific embodiments of the present application, the inorganic particles include but are not limited to ceramics, boehmite, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide, and zinc oxide, thereby improving the tensile strength and mechanical strength of the pole piece.

[0054] According to some specific embodiments of the present application, the conductive agent includes but is not limited to superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, thereby ensuring that there is a good electron channel between the current collector-intermediate coating-active material layer to achieve a low impedance effect.

[0055] According to some specific embodiments of the present application, the binder can be selected from polyacrylates, including but not limited to lithium polyacrylate, sodium polyacrylate, and magnesium polyacrylate. The above binders can provide abundant carboxyl groups, and the hydroxyl groups on the surface of the active material, conductive agent, and current collector are tightly bonded under the action of hydrogen bonds. Polyacrylates hardly swell in carbonate electrolyte solvents and have good chemical stability; polyacrylates have excellent deformation flexibility, but insufficient electronic conductivity and mechanical strength. When used alone, they will hinder the electron transmission from the current collector foil to the active material layer, and are prone to chain breaking and decomposition as the positive electrode active material layer deforms during charging and discharging. Therefore, the mixed conductive agent provides a good electron channel between the current collector-bottom coating-active material layer to achieve a low impedance effect; and the inorganic particles are mixed so that the overall membrane has high tensile strength, improves mechanical strength, and avoids the risk of deformation and fracture of the current collector caused by phase change of the positive electrode active material during battery cycling.

[0056] According to some specific embodiments of the present application, the thickness of the intermediate coating is not particularly limited, and those skilled in the art can select it according to the circumstances. As some specific examples, the thickness of the intermediate coating is 1 μm-20 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc.

[0057] According to some specific embodiments of the present application, the bonding force between the intermediate coating and the positive electrode current collector is 260N / m-400N / m. As some specific examples, the bonding force between the intermediate coating and the positive electrode current collector may be 260N / m, 270N / m, 280N / m, 290N / m, 300N / m, 310N / m, 320N / m, 330N / m, 340N / m, 350N / m, 360N / m, 370N / m, 380N / m, 390N / m, 400N / m, etc.

[0058] According to some specific embodiments of the present application, during the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte conducts ions between the positive electrode sheet and the negative electrode sheet. The isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet to prevent the positive and negative electrodes from short-circuiting while allowing ions to pass through.

[0059] According to some specific embodiments of the present application, the secondary battery is a lithium-ion secondary battery.

[0060] According to some specific embodiments of the present application, the positive electrode plate includes a positive electrode current collector, an intermediate coating and a positive electrode active material layer sequentially arranged on at least one side of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material and a lithium supplement. The positive electrode active material is preferably a lithium iron phosphate material.

[0061] According to some specific embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0062] According to some specific embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0063] According to some specific embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0064] According to some specific embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the positive electrode sheet, such as inorganic particles, conductive agent and binder, are dispersed in a solvent (such as N-methylpyrrolidone, NMP) to form an intermediate coating slurry; the positive electrode active material, lithium supplement, conductive agent and binder are dispersed in a solvent (such as NMP) to form a positive electrode active material slurry; the intermediate coating slurry and the positive electrode active material slurry are sequentially coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0065] According to some specific embodiments of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material.

[0066] According to some specific embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0067] According to some specific embodiments of the present application, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.

[0068] According to some specific embodiments of the present application, the negative electrode active material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0069] According to some specific embodiments of the present application, the negative electrode active material layer may further optionally include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0070] According to some specific embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0071] According to some specific embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0072] According to some specific embodiments of the present application, the present application has no particular restrictions on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. In some embodiments of the present application, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.

[0073] According to some specific embodiments of the present application, the positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a winding process or a lamination process.

[0074] According to some specific embodiments of the present application, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0075] According to some specific embodiments of the present application, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, polybutylene succinate, etc. can be listed.

[0076] In a second aspect of the present application, the present application proposes a method for preparing the secondary battery described in the first aspect. According to an embodiment of the present application, the preparation method comprises the following steps of injecting an electrolyte:

[0077] After the first injection is completed, the second injection is performed;

[0078] The electrolyte used in the first injection is a first electrolyte, the electrolyte used in the second injection is a second electrolyte, the first electrolyte and the second electrolyte independently include cyclic carbonate compounds, and the cyclic carbonate compounds include vinylene carbonate;

[0079] The mass proportion of vinylene carbonate in the first electrolyte is M1%, and the total mass proportion of cyclic carbonate compounds is M2%; the mass proportion of vinylene carbonate in the second electrolyte is N1%, and the total mass proportion of cyclic carbonate compounds is N2%;

[0080] The M1, N1, M2, N2, n1, m1, and S satisfy:

[0081] 15N / m≤M1×S≤50N / m, 100N / m≤N1×S≤200N / m;

[0082] 0.1≤n1<M1<m1<N1≤14.

[0083] The present application adopts a secondary liquid injection method to prepare the aforementioned secondary battery, and flexibly controls the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery by separating the electrolyte components required in the battery formation stage and the electrolyte components required in the circulation stage. According to research, the local distribution characteristics of the electrolyte in the initial state determine the local distribution characteristics of the electrolyte in the subsequent working state: under the premise that the total amount of electrolyte is sufficient and the transmission is unobstructed, the local distribution ratio of the additive in the electrolyte in the initial state can qualitatively determine the local distribution ratio of the additive in the electrolyte in the subsequent working state.

[0084] The present application adopts a secondary injection process and limits n1<M1<m1<N1 in the secondary injection, which can realize the localized distribution of the electrolyte. At the same time, the upper limit of N1 is controlled to ensure that the second electrolyte has good fluidity and avoids infiltration into the battery cell cavity.

[0085] In addition, since the intermediate coating and the active material layer contain binders, they will age more rapidly with the cyclic use of the battery, causing cyclic degradation. The abundant cyclic carbonate compounds in the electrolyte can produce cross-linking copolymerization reactions with the polymers that function as binders in the positive electrode to repair broken chains. Among the cyclic carbonate compounds studied, the flexibility and rigidity structures of the cross-linked products of VC are the most balanced. Therefore, combined with the peeling force provided by the positive electrode intermediate coating, the localized content of the main additive VC is designed. The implementation method is also to regulate the relationship between the VC content M1 and M2 and S in the one-shot and two-shot electrolytes, that is, 15N / m≤M1×S≤50N / m, 100N / m≤N1×S≤200N / m. When S is lower, M1 and M2 tend to have high content, conversely, when S is higher, M1 and M2 tend to have low content; when M1×S and N1×S are too low, the stability of the positive electrode bottom coating cannot be maintained after the cycle, and the technical effect cannot be achieved; when M1×S and N1×S are too high, the positive electrode impedance is seriously deteriorated, resulting in an increase in the positive electrode potential and a decrease in the negative electrode potential during charging and discharging. At this time, the decomposition of the electrolyte at the positive and negative electrodes is intensified, and the ion channel is broken during the cycle, resulting in a diving attenuation of the cycle capacity. M1×S can be 15N / m, 20N / m, 25N / m, 30N / m, 35N / m, 40N / m, 45N / m, 50N / m, etc., and N1×S can be 100N / m, 110N / m, 120N / m, 130N / m, 140N / m, 150N / m, 160N / m, 170N / m, 180N / m, 190N / m, 200N / m, etc.

[0086] According to an embodiment of the present application, the first electrolyte and the second electrolyte independently include cyclic carbonate compounds, and the cyclic carbonate compounds include vinylene carbonate, that is, the types of cyclic carbonate compounds in the first electrolyte and the second electrolyte may be the same or different, but both should contain vinylene carbonate.

[0087] According to an embodiment of the present application, M1, N1, M2, and N2 satisfy at least one of the following conditions: M1 / M2 - N1 / N2 < 0; 0.01 ≤ M1 / M2 ≤ 0.2; 0.1 ≤ N1 / N2 ≤ 0.6. Compared with the used battery cell, the intermediate coating in the positive electrode of the dry battery cell is not affected by cycling and the adhesion force does not decrease. Therefore, the first electrolyte (i.e., the first injection of electrolyte) is mainly used for forming SEI on the negative electrode and filling pores. The ratio of VC to cyclic carbonates M1 / M2 does not need to be particularly high. Cyclic carbonate compounds such as EC, VC, VEC, and FEC can meet the requirement of initial SEI stability. Therefore, in combination with the stripping force of the positive electrode, M1 / M2 in the first injection is set within a specified range. The second electrolyte (i.e., the second injection of electrolyte) has the ability to repair the aged positive electrode binder and intermediate coating, which determines whether the battery can work stably for a long time. Therefore, a high content of VC, N1, is necessary. At the same time, since the second electrolyte also needs to play a role in maintaining long cycling, the unconsumed part of the first electrolyte after formation is mixed with the second electrolyte to jointly form the free electrolyte in the initial state. Only when there is sufficient cyclic carbonate in the free electrolyte can the functions of SEI repair and ion channels be ensured. Therefore, the relationship between N1 / N2 within the above range and M1 / M2 < N1 / N2 is set.

[0088] Specifically, M1 / M2 can be 0.01, 0.05, 0.1, 0.15, 0.2, etc. N1 / N2 can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, etc.

[0089] According to an embodiment of the present application, the mass ratio of the first electrolyte to the second electrolyte is (6:4) to (8:2). As some specific examples, the mass ratio of the first electrolyte to the second electrolyte can be 6:4, 7:3, 8:2, etc. This can improve the cycling performance of the battery. The first injection (the first electrolyte injection) is mainly used for formation to form the initial SEI layer, and the second injection (the second electrolyte injection) is mainly used to supplement the electrolyte amount required for cycling. Therefore, the mass of the first electrolyte needs to satisfy the full wetting of the positive and negative electrode plates, and the mass of the second electrolyte needs to meet the consumption required for cycling. When the mass ratio of the first electrolyte to the second electrolyte is lower than 6:4, the injection amount during the first injection is not sufficient for full wetting, and the obtained SEI protection layer during formation is uneven. After the second injection, the areas without SEI formation are electronically conductive with the electrolyte, resulting in the decomposition and accumulation of by-products of the electrolyte. If the mass ratio of the first electrolyte to the second electrolyte is too high, that is, greater than 8:2, the proportion of the second injection is low, and the components of the free electrolyte mainly come from the unconsumed electrolyte components of the first injection, which are basically the same as those of the non-free electrolyte components. In such a ratio, the second injection is basically no different from the traditional first injection, and it is difficult to achieve the design of localized electrolyte.

[0090] According to an embodiment of the present application, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5g / Ah to 5g / Ah. As some specific examples, the sum of the injection coefficients of the first electrolyte and the second electrolyte may be 2.5g / Ah, 3g / Ah, 3.5g / Ah, 4g / Ah, 4.5g / Ah, 5g / Ah, etc., preferably 3.5g / Ah to 4.5g / Ah. Specifically, the injection coefficient (injection amount / cell capacity) represents the electrolyte demand. For energy storage batteries, a higher injection coefficient can maintain a long cycle life. The present application limits the sum of the injection coefficients of the two injections within a suitable range, which can achieve sufficient wetting of the diaphragm and the pole piece, and avoid swelling due to excessive electrolyte or accumulation at the bottom of the battery to cause local lithium precipitation.

[0091] According to a specific embodiment of the present application, the preparation method can be carried out through the following steps: first liquid injection, static formation, second liquid injection, high temperature aging, and capacity division to obtain the secondary battery. Among them, the static aging and formation process are not particularly limited, and it can be ensured that the infiltration is sufficient and the formation film is uniform. The battery can be fully charged and disassembled before the second liquid injection and before capacity division. Visible electrolyte is distributed at all positions of the positive and negative electrodes and the diaphragm in the battery, and there are no abnormal spots or dark marks on the negative electrode, which meets the requirements. The full charging process can be charged to 3.65V at a constant current of 0.2C.

[0092] In a third aspect of the present application, the present application provides an electric device. According to an embodiment of the present application, the electric device includes the secondary battery described in the first aspect.

[0093] According to some specific embodiments of the present application, the secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, and the like. Among them, the electric toy can include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, an electric airplane toy, and the like, and the spacecraft can include an airplane, a rocket, a space shuttle, a spacecraft, and the like.

[0094] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0095] The batteries of each embodiment and comparative example were prepared according to the following method:

[0096] (1) Preparation of positive electrode sheet:

[0097] Alumina, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 90:5:5, and an appropriate amount of solvent NMP is added and stirred for different times to obtain a coating slurry with a solid content of about 65±5%. The coating slurry is applied to the surface of the positive electrode collector aluminum foil, and a 3μm thick coating is formed after drying. The adhesion between the coating and the current collector is 300±50N / m. For experiments without coating design, there is no such step. By using coating slurries stirred for different times, positive electrode sheets with different peeling forces are prepared, and the peeling force of the positive electrode sheets is tested to obtain the design parameters S (N / m) in Table 1. In the experiments in Tables 2 and 3, the same coating design as that in Examples 1-2 in Table 1 is adopted.

[0098] The positive electrode active material lithium iron phosphate (LiFePO4), SP, and adhesive PVDF were dispersed in a solvent NMP at a mass ratio of 97:2.5:0.5 and mixed evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on the above-mentioned current collector aluminum foil. The coating weight per unit area of ​​the positive electrode slurry was 33 mg / cm 2 After drying, cold pressing, slitting and cutting, the positive electrode sheet is obtained;

[0099] Among them, Comparative Examples 1-1 and 1-2 in Table 1 have no positive electrode intermediate coating, and the embodiments in Table 1, the embodiments and comparative examples in Table 2, and all embodiments in Table 3 have positive electrode intermediate coating;

[0100] (2) Preparation of negative electrode sheet:

[0101] The negative electrode active material artificial graphite, conductive carbon black (SP), thickener (CMC) and binder (SBR) were dispersed in deionized water at a mass ratio of 96.5:0.5::2 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil. The coating weight per unit area of ​​the negative electrode slurry was 16 mg / cm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained;

[0102] (3) Preparation of electrolyte:

[0103] In an argon atmosphere glove box with a moisture and oxygen content of ≤0.1ppm, cyclic carbonate compounds and 12.5% ​​by mass of LiPF6 were mixed according to the designed proportions in Table 1-3, and ethyl methyl carbonate (EMC) was added to the remaining solvent components and stirred until completely dissolved. For the test groups that require secondary injection, the above method was used to prepare one injection of electrolyte and two injections of electrolyte respectively;

[0104] (4) Preparation of diaphragm:

[0105] A 16 μm polyethylene film was used as the separator;

[0106] (5) Battery assembly:

[0107] The prepared positive electrode sheet, separator and negative electrode sheet are stacked in order so that the separator is in the middle of the positive and negative electrodes to separate the positive and negative electrode sheets, and then wound into a bare battery cell. After welding the pole ears, the battery cell is assembled into an outer package, and vacuum dried after hot pressing. Then, the liquid injection process is carried out: the electrolyte is injected for the first time, the battery cell is packaged, allowed to stand, and formed, the electrolyte is injected for the second time, the battery cell is allowed to stand at high temperature, the capacity is tested, etc., and finally a soft-pack lithium-ion battery with a capacity of 3.2Ah is prepared.

[0108] Among them, Comparative Example 2-1 in Table 2 adopts a single injection process: injecting electrolyte, packaging the battery cell, standing, forming, high-temperature standing, capacity testing, etc., and finally preparing a soft-pack lithium-ion battery with a capacity of 3.2Ah. Except for the second injection process, the rest of the process remains the same.

[0109] The formation of the first injection and the second injection adopts the following steps:

[0110] (1) The battery cell was placed in a 45°C formation cabinet for 10 min and charged at 0.1C for 7 min to 1.17% SOC;

[0111] (2) Let stand for 3 min and charge at 0.2C rate to 30% SOC.

[0112] In all test groups in Table 1, the embodiments of Table 2, comparative example 2-2, and comparative example 2-3, the fixed injection coefficient is 4.0 g / Ah; the injection ratio of the first injection and the second injection is 7:3; the standing condition after the first injection is 45±5°C for 24 hours, the formation temperature is 45°C, and the standing condition after the second injection (high temperature aging) is 45±5°C for 24 hours.

[0113] In Table 3, the injection coefficient, the ratio of the first injection and the second injection are specifically listed; the temperature and time parameters in the second injection are consistent with those in Table 1 and Table 2. The electrolyte formula and positive electrode coating design of Examples 3-1 to 3-7 and Comparative Examples 3-1 to 3-3 are consistent with those of Example 1-2, and the electrolyte formula and positive electrode coating design of Example 3-8 are consistent with those of Example 2-15.

[0114] The batteries prepared in the examples and comparative examples were tested as follows:

[0115] (1) Positive electrode peeling force test:

[0116] In accordance with the requirements of GB-T2790-1995 "Adhesive 180° Peel Strength Test Method - Flexible Materials to Rigid Materials", the fully dried electrode is fixed on the upper jaw of the tensile testing machine, one end of the tape is adhered to the electrode, and the other end is folded 180° and fixed on the lower jaw of the tensile testing machine. It is pulled apart at the test rate specified in the above standard, and the peeling force (N / m) is measured by the force required to continuously peel the tape from the electrode.

[0117] (2) Test of free electrolyte composition:

[0118] Discharge the battery with outer packaging with a current of 0.05C to 0% SOC (2.5V), cut a notch of about 0.5cm on the right side of the battery facing the positive column, and cut the same notch on the right side facing the negative column, ensuring that the two notches are on the diagonal line, and pour the free electrolyte into the fluoride bottle from the small opening on the side of the positive column until intermittent dripping flows down and count for 30s.

[0119] Gas chromatography-mass spectrometry (GC-MS) was used to test the types and relative mass contents of VC and other organic components in the collected electrolyte.

[0120] Ion chromatography (IC) was used to test the relative mass content of lithium salt in the collected electrolyte.

[0121] (3) Non-free (pore) electrolyte test:

[0122] Remove the outer packaging, take out a single bare cell, quickly peel off the electrode, put it into an aluminum-plastic bag, add enough acetonitrile solvent to completely immerse the electrode, seal the aluminum-plastic bag containing acetonitrile solvent and electrode, and let it stand at 35±10℃ for 3 days.

[0123] GC-MS was used to collect the types and relative mass contents of VC and other organic components in the electrolyte.

[0124] (4) Cyclic performance test:

[0125] Charge to 3.65V at 0.5P constant power at 25℃, then discharge to 2.5V at 0.5P constant power. The capacity of the Xth cycle of charge and discharge is recorded as CCx and DCx, until X=1000, and the capacity value of each cycle is recorded.

[0126] The battery cycle life is evaluated by the cycle capacity retention rate λ, λ = DC 1000 / DC3.

[0127] Table 1

[0128]

[0129] Table 1

[0130]

[0131]

[0132] Table 1 evaluates the impact of the localized distribution characteristics of VC and EC as key components in the electrolyte on the battery cycle performance. By comparing Comparative Example 1-1 and Comparative Example 1-2, it can be seen that secondary injection is required to make the electrolyte meet the localized design parameters m1 / m2>n1 / n2. When the above formula cannot be met, the battery cell cycle performance is poor. This is because (m1 / m2)-(n1 / n2) is greater than 0 to ensure that the proportion of VC in the free electrolyte is continuously higher than the proportion of VC in the non-free electrolyte. Such a design can maintain sufficient VC in the free electrolyte, otherwise the VC in the free electrolyte is not enough to dominate the repair of the bonding ability of the positive electrode plate and the primer.

[0133] By comparing Comparative Example 1-2 and Example 1-1, it can be seen that the positive electrode primer is required to make the stripping force of the active material layer of the pole piece meet the matching of the electrolyte components. When the positive electrode primer is not introduced, the S value is low (S is 4N / m in Comparative Example 1-2, and S is 15N / m in Example 1-1), and M1×S and N1×S therefore exceed the lower limit of the specified range, and the battery cell cycle is poor. This is because the binder in the positive electrode ages more rapidly with the cyclic use of the battery, the binding effect on the internal stress of the particles decreases, and the bonding force between the active material layer and the current collector is lacking, causing problems such as expansion, contraction, and demolding of the pole piece.

[0134] It can be seen from Examples 1-1 to 1-4 and Comparative Examples 1-3 to 1-5 that the localized design (m1 / m2)-(n1 / n2) of VC and EC in the electrolyte is greater than 0, which can effectively improve the cycle performance; by adjusting the peeling force S of the active material layer of the electrode, the VC content M1 and M2 in the first and second injections, so that M1×S and N1×S fall within the limited range, the value of the localized design (m1 / m2)-(n1 / n2) can be affected. Although M1, M2, and S take conventional values ​​individually, they cannot be satisfied in the relationship, which means that the localized electrolyte design cannot be achieved and the cycle performance is poor. In Comparative Example 1-4, (m1 / m2)-(n1 / n2) is too large, which means that VC cannot effectively participate in the SEI repair process, and the cycle retention rate is not as good as that of Example 1-1 and Example 1-2. In Comparative Examples 1-5, excessive S affects the electron transport between the current collector and the active material layer, which in turn leads to excessively high resistance of the positive electrode membrane, an increase in the positive electrode potential and a decrease in the negative electrode potential during charge and discharge. At this time, the decomposition of the electrolyte at the positive and negative electrodes is intensified, and the ion channel is broken during the cycle, resulting in a sharp decline in the cycle capacity.

[0135] Table 2

[0136]

[0137] Table 2

[0138]

[0139]

[0140] Among them, " / " indicates non-existence.

[0141] Table 2 tests the influence of the characteristics of the localized distribution of cyclic carbonate compounds on the battery cycle performance under the condition that the stripping force S of the active material layer of the positive electrode sheet remains unchanged. The addition amount of VC in Comparative Example 2-1 and Comparative Example 2-2 is 3.0% after being converted according to the injection coefficient and injection ratio. Comparative Example 2-1 shows that the primary injection process widens the gap between the free electrolyte and the non-free electrolyte in terms of VC. The electrolyte satisfies the localized design parameter m1 / m2 < n1 / n2, and the cycle performance of the battery cell is poor. Comparative Example 2-2 shows that in the secondary injection process, but all VC is placed in the first-injected electrolyte, and the proportion of VC in the free electrolyte is insufficient. Similarly, m1 / m2 < n1 / n2, and the cycle performance of the battery cell is poor. In Comparative Example 2-3, VC is not used in both the first-injected and second-injected electrolytes. Although the alternative additive FEC is introduced, there is an obvious gap in the cycle capacity retention rate compared with the VC system. It can be inferred that VC plays an irreplaceable key role in long-term cycling.

[0142] It can be found from Comparative Example 1-2, Comparative Examples 2-4 to 2-14, Examples 2-1 to 2-8, and Example 2-16 that by adjusting the contents of VC and EC in the electrolyte of the secondary injection, the localized differential distribution of VC and EC in the free state and the non-free state can be achieved. In Comparative Examples 2-4, 2-5, 2-12, and 2-14, m1 / m2 < n1 / n2. In Comparative Example 2-13, (m1 / m2) - (n1 / n2) > 0.2, and the cycle performance is poor. In Comparative Examples 2-6 and 2-8, there are problems of excessive or too low m1 or n1, and the cycle performance is poor. This is because when m1 and n1 are too high, the content of VC in the free or non-free electrolyte is too much, and VC continuously and massively participates in the reduction reaction during cycling, resulting in a sharp increase in R SEI sharply increasing and deteriorating the cycle capacity. Or when m1 and n1 are too low, the content of VC in the free or non-free electrolyte is insufficient, and VC cannot play the effect of repairing the positive electrode binder layer during cycling, resulting in the stripping of the positive electrode active material after long-term cycling, thereby affecting the cycle performance.

[0143] By comparing Examples 2-9 to 2-14, it can be found that by adjusting the type and content of cyclic carbonates in the electrolyte of the secondary injection, the localized distribution characteristics of the electrolyte can also be affected. From the content of VC and other cyclic carbonates in the free state and the non-free state, it can be found that there is no absolute physical barrier between the free electrolyte and the non-free electrolyte. The unconsumed part of the first injection of electrolyte merges with the second injection of electrolyte to form the free electrolyte in the initial state. Similarly, when the non-free electrolyte is insufficiently consumed, it will automatically absorb the free electrolyte as a supplement. Therefore, only in one injection or only in two injections. The components can exist in the free and non-free electrolytes at the same time, but there are local differences in content. In addition to VC, other different cyclic carbonates, such as PC, FEC, VEC and other mixed ECs use two or more, which does not affect the application of the principles of this application, and therefore has a universal effect on the improvement of the cycle.

[0144] Embodiment 2-14 and Embodiment 2-15 are designed according to the localized electrolyte in accordance with the technical requirements, and the positive electrode primer reaches the designed M1×S and M2×S, which can achieve an ideal effect of up to 90%.

[0145] Table 3

[0146]

[0147]

[0148] Table 3

[0149]

[0150] Table 3 tests the effects of the secondary injection electrolyte injection coefficient and injection mass ratio on the localized distribution of cyclic carbonate compounds in the free electrolyte and non-free electrolyte, as well as the effects on the cycle performance.

[0151] In Comparative Example 3-1, the injection mass ratio was too low, and the separator and the electrode sheet could not be fully wetted, resulting in a lack of film formation protection in the local area of the electrode sheet that did not enter the electrolyte during the formation stage, manifested as m1 / m2 < n1 / n2; in Comparative Example 3-2, swelling occurred due to excessive electrolyte volume, and the redundant electrolyte would accumulate at the bottom of the battery, causing lithium deposition. At this time, (m1 / m2) - (n1 / n2) exceeded the upper limit requirement. Considering the influence on the actual cycle capacity retention rate, the injection coefficient of the sum of the first-injection electrolyte and the second-injection electrolyte was limited to 2.5 g / Ah to 5 g / Ah. In Comparative Example 3-3, since the injection volume ratio of the first and second injections was too low, that is, less than 6:4, the injection volume during the first injection was not sufficient to fully wet, and the SEI protective layer obtained during formation was uneven. After the second injection, the area without SEI formation was electronically conductive with the electrolyte, resulting in the decomposition and accumulation of by-products of the electrolyte; in Comparative Example 3-4, the injection volume ratio of the first and second injections was too high, that is, greater than 8:2, then the proportion of the second injection was low, and the free electrolyte mainly came from the unconsumed VC and EC in the first injection, and there was no significant difference from the content of the non-free electrolyte. In such a ratio, the second injection was basically no different from the traditional first injection, and it was difficult to achieve the design of the localized electrolyte. Therefore, the mass ratio range of the electrolyte for the first injection and the second injection was limited to 6:4 to 8:2.

[0152] It can be seen from Examples 3-1 to 3-6 that within the appropriate injection coefficient and injection mass ratio range, the influence degree of the lithium salt distribution in the non-free electrolyte and the free electrolyte is very small and can be ignored, and the solution provided by this application can still be realized. Among them, the injection coefficient is preferably 3.5 g / Ah to 4.5 g / Ah.

[0153] Based on Example 2-15, Example 3-7 with refined adjustment of the injection coefficient and the mass ratio of the second injection further improved the safety performance of the thermal runaway test and the cycle capacity retention rate, up to 93%. Since the test group was an electrolyte system without using additives of other functional group types, the long cycle life of the lithium-ion battery could be achieved at low cost; when additives of other functional group types were further introduced into the electrolyte of the test group, it was not mutually exclusive with the solution of this application, so it could be predicted that the cycle performance of the battery could be further improved.

[0154] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0155] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; The electrolyte includes a free electrolyte and a non-free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the diaphragm; The non-free electrolyte and the free electrolyte include cyclic carbonate compounds, and the cyclic carbonate compounds include vinylene carbonate; Wherein, the mass proportion of vinylene carbonate in the free electrolyte is m1%, and the total mass proportion of other cyclic carbonate compounds except vinylene carbonate is m2%; The mass proportion of vinylene carbonate in the non-free electrolyte is n1%, and the total mass proportion of other cyclic carbonate compounds except vinylene carbonate is n2%; m1, m2, n1, n2 satisfy 0<(m1 / m2)-(n1 / n2)≤0.2; The positive electrode sheet includes a positive electrode current collector and an intermediate coating and a positive electrode active material layer sequentially arranged on at least one side surface of the positive electrode current collector. The peeling force between the positive electrode active material layer and the intermediate coating is S, and S satisfies 10N / m≤S≤30N / m.

2. The secondary battery according to claim 1, characterized in that: The m1 and n1 satisfy 0.5≤m1≤5, 0.2≤n1≤3.

3. The secondary battery according to claim 1, characterized in that: The cyclic carbonate compounds also include at least one of propylene carbonate, ethylene carbonate, butylene carbonate, methyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, ethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, propyl vinylene carbonate, 1,2-dipropyl vinylene carbonate, phenyl vinylene carbonate, 1,2-diphenyl vinylene carbonate, vinyl ethylene carbonate, divinyl ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, and 3,3,3-trifluoropropylene carbonate.

4. The secondary battery according to claim 1, characterized in that: The intermediate coating comprises inorganic particles, a conductive agent and a binder; And / or, the inorganic particles include at least one of ceramic, boehmite, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide, and zinc oxide; and / or, the conductive agent comprises at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; and / or, the binder comprises polyacrylate; And / or, the polyacrylate includes at least one of lithium polyacrylate, sodium polyacrylate, and magnesium polyacrylate.

5. The secondary battery according to claim 1, characterized in that: The intermediate coating satisfies at least one of the following conditions: The thickness of the intermediate coating is 1 μm-20 μm; The bonding force between the intermediate coating and the positive electrode current collector is 260N / m-400N / m.

6. A method for preparing a secondary battery according to any one of claims 1 to 5, characterized in that: The steps of injecting electrolyte include: After the first injection is completed, the second injection is performed; The electrolyte used in the first injection is a first electrolyte, the electrolyte used in the second injection is a second electrolyte, the first electrolyte and the second electrolyte independently include cyclic carbonate compounds, and the cyclic carbonate compounds include vinylene carbonate; The mass proportion of vinylene carbonate in the first electrolyte is M1%, and the total mass proportion of cyclic carbonate compounds is M2%; the mass proportion of vinylene carbonate in the second electrolyte is N1%, and the total mass proportion of cyclic carbonate compounds is N2%; The M1, N1, M2, N2, n1, m1, and S satisfy: 15N / m≤M1×S≤50N / m, 100N / m≤N1×S≤200N / m; 0.1≤n1<M1<m1<N1≤14.

7. The preparation method according to claim 6, characterized in that: The M1, N1, M2, and N2 satisfy at least one of the following conditions: M1 / M2-N1 / N2<0; 0.01≤M1 / M2≤0.2; 0.1≤N1 / N2≤0.

6.

8. The preparation method according to claim 6, characterized in that: The mass ratio of the first electrolyte to the second electrolyte is (6:4) to (8:2).

9. The preparation method according to claim 6, characterized in that: The sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5 g / Ah to 5 g / Ah.

10. An electrical device, characterized in that: The electrical device comprises the secondary battery according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Conductive coating slurry as well as preparation method and application thereof

    CN113248989A

  • Lithium ion battery secondary injection electrolyte and lithium ion battery

    CN118507809A